InSe monolayer: synthesis, structure and ultra-high second-harmonic generation. (20th March 2018) - Zhou, Jiadong; Shi, Jia; Zeng, Qingsheng; Chen, Yu; Niu, Lin; Liu, Fucai; Yu, Ting; Suenaga, Kazu; Liu, Xinfeng; Lin, Junhao; Liu, Zheng
Abstract: III–IV layered materials such as indium selenide have excellent photoelectronic properties. However, synthesis of materials in such group, especially with a controlled thickness down to monolayer, still remains challenging. Herein, we demonstrate the successful synthesis of monolayer InSe by physical vapor deposition (PVD) method. The high quality of the sample was confirmed by complementary characterization techniques such as Raman spectroscopy, atomic force microscopy (AFM) and high resolution annular dark field scanning transmission electron microscopy (ADF-STEM). We found the co-existence of different stacking sequence ( β - and γ -InSe) in the same flake with a sharp grain boundary in few-layered InSe. Edge reconstruction is also observed in monolayer InSe, which has a distinct atomic structure from the bulk lattice. Moreover, we discovered that the second-harmonic generation (SHG) signal from monolayer InSe shows large optical second-order susceptibility that is 1–2 orders of magnitude higher than MoS2, and even 3 times of the largest value reported in monolayer GaSe. These results make atom-thin InSe a promising candidate for optoelectronic and photosensitive device applications.